2016
DOI: 10.1080/10408444.2016.1220916
|View full text |Cite
|
Sign up to set email alerts
|

Sarin (GB, O-isopropyl methylphosphonofluoridate) neurotoxicity: critical review

Abstract: Sarin (GB, O-isopropyl methylphosphonofluoridate) is a potent organophosphorus (OP) nerve agent that inhibits acetylcholinesterase (AChE) irreversibly. The subsequent build-up of acetylcholine (ACh) in the central nervous system (CNS) provokes seizures and, at sufficient doses, centrally-mediated respiratory arrest. Accumulation of ACh at peripheral autonomic synapses leads to peripheral signs of intoxication and overstimulation of the muscarinic and nicotinic receptors, which is described as “cholinergic cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 215 publications
0
69
0
Order By: Relevance
“…Pittel et al, 2006Pittel et al, , 2018. Acute exposure to OPs results in cholinergic hyperactivation and causes a set of predictable and well-documented toxic signs: hypersecretion, miosis, headache, fasciculations, tremors, convulsions, respiratory distress, and death (Bakry et al, 1988;Bajgar, 1997;McDonough and Shih, 1997;Shih et al, 1991Shih et al, , 2003Hájek et al, 2004;Bajgar et al, 2008;Sirin et al, 2012;Abou-Donia et al, 2016;Reddy and Colman, 2017;Pittel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pittel et al, 2006Pittel et al, , 2018. Acute exposure to OPs results in cholinergic hyperactivation and causes a set of predictable and well-documented toxic signs: hypersecretion, miosis, headache, fasciculations, tremors, convulsions, respiratory distress, and death (Bakry et al, 1988;Bajgar, 1997;McDonough and Shih, 1997;Shih et al, 1991Shih et al, , 2003Hájek et al, 2004;Bajgar et al, 2008;Sirin et al, 2012;Abou-Donia et al, 2016;Reddy and Colman, 2017;Pittel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with these prior reports indicating acute DFP exposure inhibits CA1 glutamatergic transmission and that a substantial component of this inhibition is mediated via cholinergic receptors. More specifically, following irreversible inhibition of AChE, enhanced synaptic ACh leads to hyperactivation of mAChRs, a well-established mechanism of OP-induced neurotoxicity (Abou-Donia et al, 2016). Previous studies have shown that mAChR blockade via ATR pretreatment partially prevents DFP-induced PS1 inhibition (Ferchmin et al, 2015).…”
Section: Jpet # 263053mentioning
confidence: 99%
“…JPET # 263053 treated, acute OP-induced cholinergic hyperactivity precipitates the presentation of cholinergic crisis followed by glutamatergic-mediated persistence of seizures and ultimately death (Abou-Donia et al, 2016).…”
mentioning
confidence: 99%
“…The reactivators show an agent‐specific effectiveness and no broadband reactivator is available today. Survivors might suffer from long‐term neuropathic effects …”
Section: Introductionmentioning
confidence: 99%
“…J = 20, 3 H) 13. C-NMR { 1 H} (100 MHz, CDCl 3 ): 136.2; 128.6; 128.4; 127.8; 127.7; 127.0; 66.5; 12.6; 11.2 31 P-NMR { 1 H} (162 MHz, CDCl 3 ): 34.65 (98%).…”
mentioning
confidence: 99%